Advertising, Values and Social Change : a Sociological Analysis. - Polesana, Maria Angela (Cambridge Scholars Publisher, 2019)
This book provides a snapshot of the major social, cultural and economic changes that have taken place in the contemporary consumer society following the global financial crisis of 2008. It discusses brands, consumption patterns and advertising, and highlights their symbolic component. Markets are conversations, as the Cluetrain Manifesto pointed out as early as 2000, and this is all the more so today in our increasingly digitalized society. Advertising, therefore, needs to attune products to the most interesting conversations, those that are consistent with the new sensibility of the individu.